68Ga-FAPI PET in detection of 18F-FDG PET Negative Cholangiocarcinoma: A Case Report on Alternative Molecular Imaging in Biliary Tract Malignancy - Sharjeel Usmani; Anjali Jain; Khulood al Riyami; Asiya al Busaidi; Asim Jamal Shaikh (Journal of the Pakistan Medical Association, 2025)
Fibroblast activation protein inhibitors (FAPI) PET is a new imaging approach that targets the cell population in the tumour surrounding stroma, particularly cancer-associated fibroblasts, rather than tumour cells. 68Ga-FAPI PET/CT FAPI PET/CT provides better lesion characterisation due to a higher tumour-to-background ratio and exhibits high diagnostic accuracy, especially for cancers that exhibit low-to-moderate uptake of 18F-FDG. We report the case of a 77-year-old woman with known renal cell carcinoma treated ten years ago, and recently presented with cholangitis and a liver lesion. 18FDG PET-CT showed a mild hypermetabolic lesion at segment V. 68Ga-FAPI PET/CT was performed for further assessment. 68Ga-FAPI PET/CT demonstrates an intensely tracer avid lesion at hepatic segment V. These findings are likely due to primary cholangiocarcinoma. Biopsy confirms intrahepatic cholangiocarcinoma. 68Ga-FAPI PET/CT FAPI PET/CT provides better lesion characterization due to a higher tumor-to-background ratio and exhibits high diagnostic accuracy in cholangiocarcinoma. Keywords: 68Ga-FAPI PET/CT; Cholangiocarcinoma; Fibroblast activation protein; cancer-associated fibroblasts Biliary Tract Malignancy.